Cardiac steatosis in patients with dilated cardiomyopathy. Issue 14 (24th April 2014) - Granér, Marit; Pentikäinen, Markku O; Nyman, Kristofer; Siren, Reijo; Lundbom, Jesper; Hakkarainen, Antti; Lauerma, Kirsi; Lundbom, Nina; Nieminen, Markku S; Petzold, Max; Taskinen, Marja-Riitta
Abstract : Objective: Ectopic fat accumulation within and around the heart has been related to increased risk of heart disease. Limited data exist on cardiac adiposity in subjects with dilated cardiomyopathy (DCM). The aim of the study was to examine the components of cardiac steatosis and their relationship to LV structure and function in non-diabetic DCM patients. Methods: Myocardial and hepatic triglyceride (TG) contents were measured with 1.5 T magnetic resonance spectroscopy (MRS), and LV function, visceral adipose (VAT) and abdominal subcutaneous tissue (SAT), epicardial and pericardial fat by MRI in 10 non-diabetic men with DCM and in 20 controls. Results: In face of comparable intra-abdominal fat depots, myocardial TG [0.41% (0.21–2.19) vs 0.86% (0.31–2.24), p=0.038] was markedly lower and epicardial (895 mm 2 ±110 vs 664 mm 2 ±180, p=0.002) and pericardial fat [2173 mm 2 (616–3673) vs 1168 mm 2 (266–2319), p=0.039] depots were larger in patients with DCM compared with controls. In subjects with DCM, the LV global function index was decreased to a greater extent than the LV EF [21%±6 vs 34% (16–40)]. Conclusions: Myocardial TG content decreased and epicardial and pericardial fat depots increased in non-diabetic subjects with DCM. Although recognised as a site of ectopic fat accumulation, the derangement of myocardial TG seems to play a specific role in the myocardial energy metabolism in congestive heart failure.